Priestia veravalensis sp. nov., isolated from coastal sample - Wagh, Vasudev S.; Ram, Hari; Dastager, Syed G. (Archives of Microbiology, 2021)
The taxonomic position of two isolates, SGD-V-76(T) and SGD-M-37, isolated from sediment sample of Veraval coast, India, was examined using the polyphasic taxonomic approach. The morphological and chemotaxonomic characteristics of these two organisms are typical of the genus Priestia. The phylogenetic analyses performed using almost complete 16S rRNA gene sequences demonstrated that the isolate belongs to the Bacillaceae family, and forms a clade within the cluster containing Priestia flexus MTCC 2909(T), Priestia aryabhattai B8W22(T) and Priestia megaterium KCTC 3007(T) and both strains showed highest similarity of > 98% with 3-29 nucleotide differences. The cell wall contained meso-diaminopimelic acid as the diagnostic diamino acid. The predominant isoprenoid quinone was MK-7 and the G + C content of strains was 37.5-37.7 mol%. However, the DNA-DNA hybridization and the phenotypic characteristics revealed that, the strain SGD-V-76(T) and strain SGD-M-37 are similar species but different from any known Priestia species with ANI values of 79.2, 79.3 and 79.2 and the dDDH values of 17.7, 17.8 and 18.0% respectively. On the basis of phenotypic characteristics, phylogenetic analysis and the results of biochemical and physiological tests, and genomic data strain SGD-V-76(T) was clearly distinguished from closely related members of the Priestia genus. Based on the above data analysis strain SGD-V-76(T) (= DSM28242(T) = KCTC33802(T) = CIP111056(T) = NCIM5510(T)) represents a novel species of the genus Priestia, and we propose the name Priestia veravalensis sp. nov.
Keywords: Coastal sediment; genome; Priestia; Veraval